2020
DOI: 10.5937/bnhmb2013087n
|View full text |Cite
|
Sign up to set email alerts
|

Material on the annotated checklist of vascular flora of Serbia: Nomenclatural, taxonomic and floristic notes II

Abstract: The paper propose nine new nomenclature combinations and indicate eight new synonyms. There are 12 taxa (species and subspecies) of vascular flora which are new for the flora of Serbia (of which nine are autochthonous and three 88 N iketić, M. etal. : Annotated Checklist of Vascular Flora of Serbia II allochtonous plants). An old or unreliable literature records for three autochthonous and one allochthonous plant in the flora of Serbia has been confirmed. Eight plant taxa are a novelty for proper Serbia, Vojvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Therefore, its current distribution is very fragmented and is often updated. For example, in Europe it was recently found in Germany after more than a century (Eitel et al 2007) and some new records for Serbia were indicated (Niketić et al 2018) (Figure 4A). In Italy, F. lachenalii is a very rare species (Pignatti et al 2017) and its presence has been confirmed in few regions (Bartolucci et al 2018).…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, its current distribution is very fragmented and is often updated. For example, in Europe it was recently found in Germany after more than a century (Eitel et al 2007) and some new records for Serbia were indicated (Niketić et al 2018) (Figure 4A). In Italy, F. lachenalii is a very rare species (Pignatti et al 2017) and its presence has been confirmed in few regions (Bartolucci et al 2018).…”
Section: Discussionmentioning
confidence: 86%
“…The same combination has been published in Niketić et al (2020), but the basionym was not clearly indicated (erroneously "sparsum" instead "djimilense") making it invalid (Art. 41.5.…”
Section: Introductionmentioning
confidence: 87%
“…This paper represents a third continuation of the inventory of the flora of Serbia (Niketić et al 2018a(Niketić et al , 2020 with nomenclatural, taxonomic and floristic notes related to taxa from the Liliopsida and Magnoliopsida groups, as well as some novelties that have not been published in An annotated checklist of vascular flora of Serbia 1 because in the meantime some significant findings for the flora of Serbia or certain administrative units have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Anacamptis laxiflora in Serbia was dubious until recent findings near the town of Preševo in Southern Serbia (Niketić et al 2018) and near the city of Priština in the Kosovo region (Niketić et al 2020). However, previous literature data could not be confirmed by the herbarium specimens (Djordjević et al 2018(Djordjević et al , 2021.…”
mentioning
confidence: 96%